2022
DOI: 10.3390/nu14071389
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Literature Review of the Relation between Nutrition and ASD Symptoms in Children

Abstract: Autism spectrum disorder (ASD) is characterized by impairments in social interaction, communication skills, and repetitive and restrictive behaviors and interests. Even though there is a biological basis for an effect of specific nutrition factors on ASD symptoms and there is scientific literature available on this relationship, whether nutrition factors could play a role in ASD treatment is unclear. The goal of the current literature review was to summarize the available scientific literature on the relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 92 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…Due to the widespread nutritional deficiency and metabolic imbalance in ASD, some researchers focused on the supplements of nutrition or change of diet in the treatment of ASD, which includes vitamin D, omega-3 fatty acid, folinic acid, probiotics, coenzyme Q10, gluten free diet, etc. However, the evidence for the relation between supplements nutrition or change of diet and ASD symptoms in childhood is generally insufficient ( 78 ). Other promising treatments include fecal microbiota transplantation, hyperbaric oxygen, Tomatis sound, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the widespread nutritional deficiency and metabolic imbalance in ASD, some researchers focused on the supplements of nutrition or change of diet in the treatment of ASD, which includes vitamin D, omega-3 fatty acid, folinic acid, probiotics, coenzyme Q10, gluten free diet, etc. However, the evidence for the relation between supplements nutrition or change of diet and ASD symptoms in childhood is generally insufficient ( 78 ). Other promising treatments include fecal microbiota transplantation, hyperbaric oxygen, Tomatis sound, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Further, consumption of foods with gluten and casein results in a pronounced presentation of ASD in young children. Modifying nutrient intake to gluten-free and casein-free (GFCF) has been proven effective in controlling the condition and suppressing its manifestation [12]. Hence, a particular nutrition plan is suggested for children with ASD (see Fig 3).…”
Section: Offspring Genetic and Nutritionmentioning
confidence: 99%
“…It has become evident that nutrition affects early brain development and contributes to later mental health in youth with ASD. Indeed, many dietary agents are important for both the structural integrity of the brain and functional processes such as synaptogenesis and neurotransmitter synthesis [17]. Despite the lack of robust evidence to provide practical nutrition guidelines, several articles have suggested that specific dietary interventions may play a role in the management of some symptoms, functions, and clinical domains in patients with ASD [18,19].…”
Section: Introductionmentioning
confidence: 99%